Mapping the flow of commercial broiler day-old chicks in Kenya - Ibayi, Eugine L.; Nyambura, Jane N.; Guyo, Boru A.; Moodley, Arshnee; Muloi, Dishon M. (Frontiers in Veterinary Science, 2025)
IntroductionPoultry production is a significant contributor to economic growth and food security in Kenya. Reliable data on day-old chicks (DOCs) production and distribution are essential for formulating effective national policies on poultry production and animal health delivery. Here, we describe the commercial broiler DOCs production, distribution, and associated animal health and antibiotic use practices in Kenya.MethodsData were collected through focus group discussions, individual interviews, and key informant interviews involving three DOCs producers, 128 distributors, two government regulatory agencies, one poultry producers’ association and 128 farmers.ResultsAcross the DOCs production pyramid, animal health and biosecurity practices varied, with stronger management observed in parent stock (PS) than in commercial stock (CS) production facilities. DOCs distribution followed either vertically integrated systems for largescale broiler farms—owned by the CS producers or contracted farms—or horizontal systems involving numerous small-scale distributors. Veterinary drug stores were the main distributors (96%) of CS DOCs to farmers. Veterinary authorities routinely audited PS and CS hatcheries for compliance with biosecurity and animal welfare standards. However, suboptimal animal welfare practices (such as long travel times and transportation stress) and inappropriate antibiotic recommendation to farmers were observed at the distribution level during collection of CS DOCs.DiscussionThese findings provide critical evidence to guide policies on biosecurity, distribution, and animal health practices within the DOCs distribution chain. Factors such as transportation stress, poor biosecurity, and inappropriate antibiotic recommendations can compromise DOCs health, which may result in higher antibiotic use on farms. Strengthening oversight and promoting best practices across the production and distribution system would enhance the quality and health of DOCs supplied to farmers, reduce dependence on antibiotics, and support sustainable poultry production that safeguards both food security and public health.